The Nuffield Council’s green light for genome editing human embryos defies fundamental human rights law - Drabiak, Katherine (Bioethics, 2020)
In July 2018, the Nuffield Council on Bioethics released the report Genome editing and human reproduction: Social and ethical issues, concluding that human germline modification of human embryos for implantation is not ‘morally unacceptable in itself’ and could be ethically permissible in certain circumstances once the risks of adverse outcomes have been assessed and the procedure appears ‘reasonably safe’. The Nuffield Council set forth two main principles governing anticipated uses and envisions applications that may include health enhancements as a public health measure. This essay provides a critique of three aspects in the Nuffield Council’s Report: its presumption of therapeutic efficacy, its inflation of parental rights to create a certain type of child, and its reliance on a specially commissioned report that appears to distort key definitions in international law.